THE INFLUENCE OF USING SKIMMING TECHNIQUE TOWARD THE STUDENTS’ READING COMPREHENSION AMONG THE ELEVENTH GRADERS OF SMK N 3 METRO - Eka Yuniasih (Premise: Journal of English Education and Applied Linguistics, 2014)
The purpose of this research was to implement the skimming technique and analyze its influence in the student comprehending reading texts at the eleventh grade (XI TKJ) of SMK N 3 Metro. In this research the researcher gave pretest to know the students’ ability in understanding reading texts and posttest to know the result of the students’s ability in reading text after giving the skimming technique.This research was quantitative research which had been conducted in SMK N 3 Metro at the class XI TKJ and followed by 70 students as the sample. The tehnique sampling was cluster random sampling. In collectting the data the researcher used test. The researcher used the test to get the data of student’s reading comprehension through the questions which consisted of 30 multiple choices  about the reading text. This test was used to figure out whether the skimming technique was suitable and could be used by the students in comprehending the reading texts. The analysis which was used by the researcher was t-test. Finally, the data indicates that t observed  = 23.945 is higher than t table = 2.99. Therefore, it can be concluded that Ha is accepted and Ho is rejected. It means that the skimming technique influences the students’ reading comprehension at the eleventh graders of SMK N 3 Metro in the academic year of 2010/2011.